(untitled) (Research, Society and Development, 2021)
This study was done in order to evaluate the changes in flexural strength and surface roughness in dental material restorations after immersion in coffee. Bars specimens (2mm x 2mm x 25 mm) of Z100 3M/ESPE were made according to ISO 4049 using aluminum molds. After curing, the specimens were then randomly divided into five groups and conditioned at 37°C in physiological serum. In all groups, except control, samples were immersed in coffee for ten minutes daily. In group A, the samples were immersed in coffee. For group B, after to be immersed in coffee, samples were immersed in distilled water for one minute. For group C, samples were immersed in mouthwash for one minute. For group D, samples were brushing for ten minutes, with load of 250g and 4250 cycles after all treatments the samples were stored in physiological serum again. In control group, samples were only stored in physiological serum. The five groups were then divided into 2 subgroups according storage time, six and nine weeks, respectively. Flexural strength was determined using three point bending test in a universal testing machine. All the tests were carried out at a room temperature and samples were maintained in physiological serum during the test. Surface roughness measurements were made using a surface roughness tester. All data were analyzed using one-way analysis of variance (ANOVA) followed by Dunnet tests. The ANOVA indicated no difference in the means of surface roughness and significant was observed for flexural strength between control group and one group (coffee).